Case Report: A case study of positive doping control by animal-to-human drug transfer after an athlete administered medicine in spray format, containing clostebol acetate, to a pet dog - Pokrywka, Andrzej; Sitkowski, Dariusz; Surała, Olga; Gheddar, Laurie; Kintz, Pascal (Frontiers in Sports and Active Living, 2024)
The presence of a doping substance in an athlete's biological sample may not be only related to intentional pharmacological support. The unintended use of a prohibited substance may be due various reasons. This paper describes the case of a Polish canoeist preparing for the 2024 Summer Olympics in Paris who presented a positive doping test result, as a consequence of administering medication to her injured dog. The athlete used a Trofodermin cutaneous spray (containing clostebol acetate) for pet treatment, which resulted in human transfer during close contact and subsequent detection by doping authorities. To bolster the athlete's defense, it was essential to substantiate the scenario of an unconscious violation of anti-doping rules with scientific evidence. Hence, the decision was made to analyze and compare samples of the athlete's hair and her dog's fur. This investigation confirmed that clostebol absorption occurred through the skin of the hands, transfer during sleeping with the dog on the same bedding and/or inhalation (during the application of the medication, which was dispensed to the animal's paws). This defense was accepted by the Court of Arbitration for the Sport Anti-Doping Division, which subsequently found that the athlete committed an anti-doping rule violation, but under circumstances that amounted to a “no fault” scenario.